Connections between the Ras-cyclic AMP pathway and G1 cyclin expression in the budding yeast Saccharomyces cerevisiae. - Hubler, L (1993)
We have identified two processes in the G1 phase of the Saccharomyces cerevisiae cell cycle that are required before nutritionally arrested cells are able to return to proliferative growth. The first process requires protein synthesis and is associated with increased expression of the G1 cyclin gene CLN3. This process requires nutrients but is independent of Ras and cyclic AMP (cAMP). The second process requires cAMP. This second process is rapid, is independent of protein synthesis, and produces a rapid induction of START-specific transcripts, including CLN1 and CLN2. The ability of a nutritionally arrested cell to respond to cAMP is dependent on completion of the first process, and this is delayed in cells carrying a CLN3 deletion. Mating pheromone blocks the cAMP response but does not alter the process upstream of Ras-cAMP. These results suggest a model linking the Ras-cAMP pathway with regulation of G1 cyclin expression.